Human T-Lymphotropic Virus Type 1 Open Reading Frame I p12(I) Is Required for Efficient Viral Infectivity in Primary Lymphocytes - Albrecht, Björn (American Society for Microbiology, 2000)
Human T-lymphotropic virus type 1 (HTLV-1) is a complex retrovirus encoding regulatory and accessory genes in four open reading frames (ORF I to IV) of the pX region. Emerging evidence indicates an important role for the pX ORF I-encoded accessory protein p12(I) in viral replication, but its contribution to viral pathogenesis remains to be defined. p12(I) is a conserved, membrane-associated protein containing four SH3-binding motifs (PXXP). Its interaction with the interleukin-2 (IL-2) receptor β- and γ-chains implies an involvement of p12(I) in intracellular signaling pathways. In addition, we have demonstrated that expression of pX ORF I p12(I) is essential for persistent infection in rabbits. In contrast, standard in vitro systems have thus far failed to demonstrate a contribution of p12(I) to viral infectivity and ultimately cellular transformation. In this study we developed multiple in vitro coculture assays to evaluate the role of p12(I) in viral infectivity in quiescent peripheral blood mononuclear cells to more accurately reflect the virus-cell interactions as they occur in vivo. Using these assays, we demonstrate a dramatic reduction in viral infectivity in quiescent T lymphocytes for a p12 mutant viral clone (ACH.p12) in comparison to the wild-type clone ACH. Moreover, addition of IL-2 and phytohemagglutinin during the infection completely rescued the ability of ACH.p12 to infect primary lymphocytes. When newly infected primary lymphocytes are used to passage virus, ACH.p12 also exhibited a reduced ability to productively infect activated lymphocytes. Our data are the first to demonstrate a functional role for pX ORF I in the infection of primary lymphocytes and suggest a role for p12(I) in activation of host cells during early stages of infection.